Representative Patterns of Community Clean and Healthy Living Behaviors among Scabies Cases in Wolofeo - Maria Kornelia Ringgi Kuwa; Bambang Budi Raharjo; Antonia Rensiana Reong; Marianus Oktavianus Wega (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Scabies is a contagious skin condition and a persistent public health issue in many tropical regions, including Indonesia. Clean and Healthy Living Behaviors play a central role in preventing transmission, particularly in communities with limited sanitation. Objectives: This study aimed to identify community patterns of knowledge, attitudes, and practices related to Clean and Healthy Living Behaviors associated with scabies occurrence in the Wolofeo region. Methods: This descriptive quantitative study included 70 respondents selected through purposive sampling from individuals who had previously received outpatient treatment for scabies at the Wolofeo Health Center. Data were collected using a standardized questionnaire that had undergone content validation and reliability testing. Validity was supported by a CVI of 0.87, and reliability was confirmed through a pilot test yielding a Cronbach’s Alpha of 0.82. Data were analyzed descriptively using frequency and percentage distributions. Results: Most respondents demonstrated good knowledge of hygiene and scabies prevention. Attitudes toward Clean and Healthy Living Behaviors were overwhelmingly positive, with nearly all participants expressing favorable views. All respondents reported good hygiene practices, indicating strong behavioral adoption of preventive measures. Demographic characteristics, particularly adulthood and senior high school education levels, were associated with higher readiness to implement preventive behaviors. Conclusions: The community showed strong preparedness for scabies prevention through good knowledge, positive attitudes, and consistent hygiene practices. However, a small subset exhibited limited understanding and less favorable attitudes, highlighting the need for sustained health education. Future research should incorporate observational methods to validate self-reported practices and better inform targeted prevention strategies.